Effective Sedation Strategies for Pediatric MRI: A Comprehensive Analysis: Strategi Sedasi yang Efektif untuk MRI Pediatrik: Analisis Komprehensif - Ahmed Nooruldeen Abdulrahman; Wisam Adnan Mahmood; Zinah Noorulden Abdulrahman (Universitas Muhammadiyah Sidoarjo, 2024)
This study presents a structured sedation program for pediatric patients undergoing MRI, aiming to optimize safety and resource utilization. A total of 1857 children were included, with 48 admitted to the RCU, leaving 1809 for analysis. Children under 5 received oral sedation, while those 6 and older were assessed by referring physicians for sedation eligibility. The protocol involved chloral hydrate and paraldehyde, with a backup plan for intravenous sedation or general anesthesia overseen by an anesthetist consultant. Among 1039 scans, 597 were unsedated, and 442 were sedated successfully. Oral sedation failed in 50 cases (6.9%), predominantly in younger children (87% under 5 years). Notably, 2 out of 5 subjects using chloral hydrate experienced respiratory issues. This systematic approach led to efficient resource use and safe outcomes, highlighting the importance of tailored sedation protocols in pediatric imaging. Highlights: Reduced oral sedation failure rate to 6.9% in pediatric MRI. Anesthetist consultation enhances safety in MRI sedation procedures. Structured program optimizes resources and ensures safe outcomes in pediatrics. Keywords: Pediatric MRI, Sedation Program, Anesthetist Consultation, Oral Sedation, Resource Utilization